Hydrangea-like nanocellulose microspheres with high dye adsorption and drug encapsulation prepared by emulsion method. (15th November 2022) - Zhu, Hengfeng; Zhu, Enwen; Xie, Yuanyuan; Liu, Dongning; Hu, Yang; Shi, Zhuqun; Xiong, Chuanxi; Yang, Quanling
Abstract: Currently, microspheres with high adsorption capacity play a crucial role in dye adsorption and drug loading. In this study, 2, 2, 6, 6-tetramethylpiperidinyl-1-oxyl (TEMPO)-oxidized cellulose nanofibrils (TOCN) could be used to form nanocellulose microspheres by the emulsion method. The prepared hydrangea-like nanocellulose microspheres presented a stable three-dimensional network porous structure and exhibited excellent adsorption properties. The TOCN microspheres had a high adsorption capacity for methylene blue (MB) and methyl orange (MO) with the optimal adsorption capacity of 412.1 mg g −1 and 286.5 mg g −1 under neutral conditions, respectively. The TOCN microspheres displayed excellent adsorption selectivity on MB/MO mixed dyes, which could be used to selectively adsorb MB. Besides, the encapsulation rate of the positively charged drug doxorubicin hydrochloride (DOX) was as high as 93 %, and the drug loading capacity was as high as 34.5 %. Overall, our prepared nanocellulose microspheres had great potential for application in dye adsorption and drug delivery systems. Graphical abstract: Unlabelled Image Highlights: TOCN was used to form porous and hydrangea-like microspheres by emulsion method. The adsorption to methylene blue and methyl orange was 412.1 and 286.5 mg g −1 . The encapsulation rate and drug loading capacity of DOX were 93 %, 34.5 % respectively.